AICCRA Country Scaling Vision: Ghana - Tepa-Yotto, Ghislain; Yeboah, Stephen; Dalaa, Mustapha Alasan; Kyere, Reginald; Tahidu, Osman; Adomaa, Faustina Obeng (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Ghana conceptual framework to achieve country’s scaling vision was constructed around mutually reinforcing key elements interacting with one another to produce the desired outcomes: innovation (CSA/CIS), beneficiaries, enabling environment, drivers and service providers. Monitoring evaluation and the associated learning is identified as an integral part of the process. Critical decisions need to be made in terms of scaling mechanisms to embrace, advocacy and science-policy dialogues, strategic partners to engage, CSA/CIS potential to drive the outcomes, their costs and accessible financial structures and products.